2002
DOI: 10.1152/japplphysiol.00174.2002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ion transport inhibitors on MCh-mediated secretion from porcine airway submucosal glands

Abstract: Submucosal glands secrete macromolecules and liquid that are essential for normal airway function. To determine the mechanisms responsible for airway gland secretion and the interaction between gland secretion and epithelial ion transport, studies were performed in porcine tracheal epithelia by using the hillocks and Ussing techniques. No significant baseline gland fluid flux (J(G)) was measured by the hillocks technique after 3 min, and the epithelia had an average potential difference of 7.5 +/- 0.5 mV (lume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 58 publications
(65 reference statements)
2
12
0
Order By: Relevance
“…However, the kinetics of NPPB inhibition in the pig was notably slower than in all other species. These findings support previous studies on submucosal gland secretion in the pig trachea, in which NPPB inhibited methacholineand acetylcholine-induced glandular secretions more effectively than glibenclamide (25,44).…”
Section: Species-specific Differences In the Ability Of CL ؊ Channel supporting
confidence: 92%
“…However, the kinetics of NPPB inhibition in the pig was notably slower than in all other species. These findings support previous studies on submucosal gland secretion in the pig trachea, in which NPPB inhibited methacholineand acetylcholine-induced glandular secretions more effectively than glibenclamide (25,44).…”
Section: Species-specific Differences In the Ability Of CL ؊ Channel supporting
confidence: 92%
“…However, when potassium channel activation increases anion secretion, hyperpolarisation also promotes electrogenic sodium absorption ( Gao et al , 2001 ) and hence is profluid absorption. While this is so for the surface airway epithelium, it cannot apply to the Calu‐3 monolayers since no pathway for electrogenic sodium absorption exists, although the evidence for submucous glands themselves remains open ( Phillips et al , 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…mRNA for both α and β subunits of epithelial Na + channels (ENaC) are expressed in human gland ducts, and it has been suggested that these channels might be involved in the absorption of salt and water (Burch et al 1995). This notion is supported by observations that amiloride, an ENaC inhibitor, increases the rate of ACh-induced fluid secretion in porcine tracheal glands by 60% (Phillips et al 2002b).…”
Section: Mechanism Of Gland Liquid Secretionmentioning
confidence: 97%